2006
DOI: 10.3844/ajidsp.2006.153.158
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Growth Hormone Therapy in HIV-infection

Abstract: Abstract:The results of these studies suggested that the growth hormone might play a role in the management of visceral fat accumulation associated with HIV. Analysis of the treatment effect sizes in the published studies show that the effects of various doses of rhGH on trunk fat fit a dose-response characteristic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Kotler [8] reported on the effects of growth hormone (GH) therapy in HIV-infection. He showed that recombinant human growth hormone (rhGH) might play a role in the management of visceral fat accumulation associated with HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Kotler [8] reported on the effects of growth hormone (GH) therapy in HIV-infection. He showed that recombinant human growth hormone (rhGH) might play a role in the management of visceral fat accumulation associated with HIV infection.…”
Section: Introductionmentioning
confidence: 99%